Safety and immunogenicity of a new tuberculosis vaccine, MVA85A, in Mycobacterium tuberculosis-infected individuals. - Sander, C; Pathan, A; Beveridge, N; Poulton, I; Minassian, A; Alder, N; Van Wijgerden, J; Hill, A; Gleeson, F; Davies, R; Pasvol, G; Mcshane, H (2009)
RATIONALE: An effective new tuberculosis (TB) vaccine regimen must be safe in individuals with latent TB infection (LTBI) and is a priority for global health care. OBJECTIVES: To evaluate the safety and immunogenicity of a leading new TB vaccine, recombinant Modified Vaccinia Ankara expressing Antigen 85A (MVA85A) in individuals with LTBI. METHODS: An open-label, phase I trial of MVA85A was performed in 12 subjects with LTBI recruited from TB contact clinics in Oxford and London or by poster advertisements in Oxford hospitals. Patients were assessed clinically and had blood samples drawn for immunological analysis over a 52-week period after vaccination with MVA85A. Thoracic computed tomography scans were performed at baseline and at 10 weeks after vaccination. Safety of MVA85A was assessed by clinical, radiological, and inflammatory markers. The immunogenicity of MVA85A was assessed by IFNgamma and IL-2 ELISpot assays and FACS. MEASUREMENTS AND MAIN RESULTS: MVA85A was safe in subjects with LTBI, with comparable adverse events to previous trials of MVA85A. There were no clinically significant changes in inflammatory markers or thoracic computed tomography scans after vaccination. MVA85A induced a strong antigen-specific IFN-gamma and IL-2 response that was durable for 52 weeks. The magnitude of IFN-gamma response was comparable to previous trials of MVA85A in bacillus Calmette-Guérin-vaccinated individuals. Antigen 85A-specific polyfunctional CD4(+) T cells were detectable prior to vaccination with statistically significant increases in cell numbers after vaccination. CONCLUSIONS: MVA85A is safe and highly immunogenic in individuals with LTBI. These results will facilitate further trials in TB-endemic areas. Clinical trial registered with www.clinicaltrials.gov (NCT00456183).